Oncogenic BRAF mutation induces DNA methylation changes in a murine model for human serrated colorectal neoplasia. Issue 1 (2nd January 2018) - Bond, Catherine E.; Liu, Cheng; Kawamata, Futoshi; McKeone, Diane M.; Fernando, Winnie; Jamieson, Saara; Pearson, Sally-Ann; Kane, Alexandra; Woods, Susan L.; Lannagan, Tamsin R. M.; Somashekar, Roshini; Lee, Young; et al.
ABSTRACT: Colorectal cancer is a major cause of cancer death and approximately 20% arises within serrated polyps, which are under-recognized and poorly understood. Human serrated colorectal polyps frequently exhibit both oncogenic BRAF mutation and widespread DNA methylation changes, which are important in silencing genes restraining neoplastic progression. Here, we investigated whether in vivo induction of mutant Braf is sufficient to result in coordinated promoter methylation changes for multiple cancer-related genes. The Braf V637E mutation was induced in murine intestine on an FVB;C57BL/6J background and assessed for morphological and DNA methylation changes at multiple time points from 10 days to 14 months. Extensive intestinal hyperplasia developed by 10 days post-induction of the mutation. By 8 months, most mice had murine serrated adenomas with dysplasia and invasive cancer developed in 40% of mice by 14 months. From 5 months onwards, Braf mutant mice showed extensive, gene-specific increases in DNA methylation even in hyperplastic mucosa without lesions. This demonstrates that persistent oncogenic Braf signaling is sufficient to induce widespread DNA methylation changes. This occurs over an extended period of time, mimicking the long latency followed by rapid progression of human serrated neoplasia. This study establishes for the first time that DNA methylation arises slowly in direct response to prolonged oncogenic Braf signaling in serrated polyps; this finding has implications both for chemoprevention and for understanding the origin of DNA hypermethylation in cancer generally.